Efficacy and Safety of Percutaneous Transhepatic Lithotripsy Using SpyGlassDSTM Cholangioscopy for the Treatment of Difficult Stones - Salvatore Alessio Angileri; Giuseppe Pellegrino; Carolina Lanza; Jacopo Pozzi; Marco Costa; Matilde Pavan; Pierpaolo Biondetti; Serena Carriero; Velio Ascenti; Gaetano Valerio Davide Amato; Pierluca Torcia; Anna Maria Ierardi; et al. (Diagnostics)
Background/Objectives: the aim of this study was to evaluate the safety and efficacy of percutaneous transhepatic lithotripsy using the SpyGlassDSTM cholangioscopy system for the treatment of difficult stones. Methods: Retrospectively, all patients treated with percutaneous transhepatic lithotripsy using SpyGlassDSTM cholangioscopy system were analyzed. As primary outcome measures, the following data were assessed: the presence of a previous history of the hepatobiliary disease, location of stones, reasons for the choice of the procedure, previous balloon bilioplasty, type of pre-procedural imaging, procedural time, technical success, clinical success, and post-procedural complications (according to CIRSE classification). Clinical success was considered “primary” when achieved with a single treatment, and “secondary” if more than one treatment was required in the duration of follow-up. Results: 10 patients (6 males and 4 females, mean age = 64 years, SD = 22), all with cholangitis due to gallstones, underwent 11 PTL procedures using SpyGlassDSTM. Technical and clinical successes were achieved in all patients (100%). Primary success was observed in 4/10 (40%) patients, while the remaining 6/10 (60%) patients undergoing re-treatment, and all showed secondary success (100%). No periprocedural complications were observed. In 10/11 procedures (90%), no relevant adverse events were recorded within the first thirty days of follow-up. In 1/11 case (9%), mild complications (grade I according to CIRSE classification) were registered in the following days after the procedure (<30 days). Conclusions: in conclusion, the treatment of percutaneous transhepatic lithotripsy using SpyGlassDSTM cholangioscopy of difficult stones has been demonstrated as efficient and safe treatment.